Comparative Study of Conventional and Ecological Farms - Petrică ȘTEFAN; Romeo Cătălin CREȚU; Raluca Florentina CREȚU (Communications of International Proceedings, 2021)
Unlike conventional agriculture, which mainly aims to maximize economic efficiency, organic farming is three-dimensional, each of its components and features belonging to the ecological, economic or social dimension, and these dimensions are in a balanced ratio. The ecological dimension includes the quantitative and qualitative edaphic, climatic and biological potential of plants and animals, the economic one - material and financial values ​​in exploitation or conservation, and the social one - labor force in number, physical skills and knowledge about life, society, culture, agriculture and other adjacent economic activities, as well as interpersonal relation . In this study, several economic aspects were taken into account. Although the paper has its limitations - only Central and Western European countries are analyzed and only large-scale farms and farms are considered - it does offer some interesting conclusions.
Keywords: Organic Agriculture; Conventional Agriculture; Farms .